Abdominal strength in voiding cystometry: a risk factor for recurrent urinary tract infections in women. Issue 12 (December 2015) - Salinas, Jesus; Virseda, Miguel; Méndez, Santiago; Menéndez, Pablo; Esteban, Manuel; Moreno, Jesus
Abstract Introduction and hypothesis Recurrent urinary tract infections are a common condition in women. The aim of this study is the evaluation of lower urinary tract dysfunctions that are risk factors for recurrent urinary tract infections in women. Methods We conducted a case–control study in 49 women with recurrent urinary tract infections (rUTIs) and 49 control women without rUTIs, comparing the urinary symptoms and urodynamic data of both groups. Results The main significant differences between these groups were age (the women were older in the control group) and the value of abdominal pressure during voiding cystometry (this was higher in the group with rUTIs). After controlling age as a confounding factor, it was confirmed that the value of maximum abdominal pressure during voiding was the only factor to facilitate the rUTIs and the ideal cut-off was 28 cm H2 O. Conclusions Abdominal strength in the voiding phase constitutes a risk factor for recurrent urinary tract infections in women.